Search for biomarkers in an experimental model of hypoxic-ischaemic brain damage - Huecas Zarzuelo, Alejandra; Ybot González, Patricia; Sánchez Sanz, María; Smani, Younes (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2025)
Motivation: Hypoxic-ischaemic encephalopathy (HIE) results from sudden impaired brain blood flow, leading to oxygen deprivation and potential brain damage. Its incidence is neonates is 1 to 8 per 1,000 births, and despite being a rare disease, it ranks among the top 10 causes of childhood mortality in developed countries and contributes to life-long disabilities. The extent of motor, cognitive, and behavioural impairments depends on factors such as the affected brain region, duration of oxygen deprivation, and severity of the event. Therapeutic hypothermia is the primary intervention but early diagnostics are lacking, which highlights the need for advanced detection techniques. Our group’s single-cell transcriptomics (scRNA-seq) studies have analysed blood and vascular precursor responses in neonatal hypoxic-ischaemic injury. This study aims to validate scRNA-seq findings via flow cytometry, RT-qPCR and immunofluorescence, seeking for blood biomarkers. Methods: A neonatal hypoxia-ischaemia (HI) experimental model in mice was developed based on the Rice-Vannucci’s protocol. Postnatal day 7 (P7) mice underwent unilateral ligation of the left common carotid artery followed by 90 minutes hypoxia with 9% O2. 48 hours post-insult, a multiparametric analysis was conducted assessing peripheral blood via flow cytometry and brain tissue via immunofluorescence to characterise cellular and molecular responses. Results: Neonatal HI triggers neuroinflammatory and vascular alterations. Increased microglial activation (IBA1+) and leukocyte infiltration (CD45+) are expected in brain tissue, potentially modulated by CD31+ endothelial cells, which facilitate immune cell recruitment. Preliminary findings indicate increased Ki67+ proliferating cells in infarcted areas. Optimization of leukocyte (CD45, CD11b) and endothelial (CD31) staining in SHAM and HI samples is ongoing. Flow cytometry has been initiated, focusing on monocyte subsets due to previous scRNA-seq assays. An 8-colour panel has been optimized in control samples using markers: DAPI, CD45, Ly6C, Lyve1, CD172, CD36, and Siglec-F. While quantitative significance is pending, preliminary results align with previous scRNA-seq data. Conclusions: Expected findings suggest immune activation in brain tissue and peripheral blood, indicating the neuroinflammatory response after an HI episode. Aligning these results with previous transcriptomic studies could aid in developing rapid diagnostic strategies for HIE in newborns.